2009
DOI: 10.1038/bmt.2009.345
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus use in adult allogeneic stem cell transplant recipients receiving voriconazole: preemptive dose modification and therapeutic drug monitoring

Abstract: Concomitant use of tacrolimus and voriconazole, both competitive inhibitors of the CYP450 3A4 isoenzyme, requires tacrolimus dose reduction. On the basis of clinical observations, we developed a preemptive dose-reduction strategy in allograft recipients who received voriconazole to maintain tacrolimus concentrations within a target range. A total of 27 patients started i.v. tacrolimus at an average daily dose of 0.022 mg/kg on day À1 (30% lesser than the usual starting dose). The dose was reduced by 30-40% if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 18 publications
0
39
3
Order By: Relevance
“…Although the use of uniform or preemptive dose-reduction strategies of tacrolimus alone is a simple approximation due to wide interpatient variability, these are oen implemented in clinical practice in an effort to reduce time to therapeutic targets and potentially reduce the incidence of toxicity [4]. Our �ndings indicate that typical dosage adjustments following a switch from �uconazole to voriconazole may be more modest than previous estimates.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Although the use of uniform or preemptive dose-reduction strategies of tacrolimus alone is a simple approximation due to wide interpatient variability, these are oen implemented in clinical practice in an effort to reduce time to therapeutic targets and potentially reduce the incidence of toxicity [4]. Our �ndings indicate that typical dosage adjustments following a switch from �uconazole to voriconazole may be more modest than previous estimates.…”
Section: Discussioncontrasting
confidence: 53%
“…Various dosing and monitoring strategies have been suggested for patients administered voriconazole and tacrolimus concurrently who have not been receiving �uconazole. In an attempt to counteract anticipated changes in tacrolimus concentrations, Tri�lio et al described the use of a preemptive dose reduction strategy based off of 48-hour steady-state levels [4]. e authors concluded that although preemptive dose reduction was an effective strategy, subsequent therapeutic drug monitoring and the need for further drug levels were still essential.…”
Section: Introductionmentioning
confidence: 99%
“…Although the magnitude of the CYP3A-mediated drug-drug interaction seems to be related to intrinsic CYP3A activity, in practice, it is still difficult to predict the magnitude of the interaction between TAC and triazole antifungal agents. 19 To resolve this problem, because of the established facts that genetic polymorphisms in CYP2C19 have been considered to explain 30%-50% of VRCZ PK variability, 20 we investigated the contribution of genetic polymorphism in CYP2C19 and the concomitant use of LAN as additional factors influencing the hepatic interaction between TAC and VRCZ in this study. LAN is commonly used after HSCT to prevent gastroenteric disturbance and has been reported to inhibit not only CYP2C19 but also CYP3A4, resulting in a variation in blood TAC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…every 2-3 weeks) thereafter [29 ]. Upon discontinuation of the azole, the duration of the inhibitory effect depends on the triazole's half-life [3].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%